CHEMICAL AND MINERALOGICAL RESEARCH BASALT "AYDARKUL" - Rashidova Ra’no Kayimovna (Modern American Journals, 2025)
In the article, researches on structural, chemical mineralogical properties of Aydarkul basalts and their content are carried out, and the results are described. The mineralogical composition of Aydarkol basalts is studied and the results are highlighted. The results of the research were analyzed and compared with the physico -chemical composition and properties of basalt rock from other deposits. On the basis of the obtained results, opinions and conclusions were made about the possible application of Aydarkul mine basalts in the fields of production.
Keywords: Basalt, structure, mineralogical composition, texture, geological structure, crystal structure, metabasalt, diabase.